MEASURES TO PRESERVE THE ECO-BALANCE OF THE TERRITORIES AND DEVELOP ECOLOGICAL TOURISM: IN SEARCH OF PARITY - L. N. Talalova (Вестник университета)
Between the strategies for preserving the eco-balance of territories and the development of ecotourism there is a “twilight zone”, measures for the development of the latter may run counter to the former. On the example of the Republic of Tajikistan, based on relevant ratings, the author analyses the mechanisms for implementing a balanced approach to the problem (the result is the entry into the international ecotourism market, the creation of infrastructure). The paper considers the reasons that prevent the Republic of Uzbekistan from achieving similar results, studies tactics on specific examples. National parks are losing cultural monuments due to economic activities and tourism constitute the basis of socio-economic development of the territory with the diversification of the rural economy and provide jobs for the local population, and yet actualize raised in the article the problem of museumification of landscapes –conversion of natural objects in the objects of the Museum display. The study showed that the inclusion of several cultural objects in the UNESCO World Heritage List in 2019, the adoption of specific measures for their conservation (Road Map – 2020) will allow the Republic of Uzbekistan to transform areas with a high level of landscape and recreational potential into centers of regional ecotourism, and with regard to cultural monuments, this will be minimal losses.